Place of delivery and its determinants among women in rural and urban communities in Kano State, Nigeria - Iliyasu, Usman; Musa, Zakka; Shehu Ibrahim, Aliyu; Mohammed, Nazeef; Rabi’u, Abba; Ibrahim Kurba, Ibrahim; Kalle Isma’il, Musa; Aliyu Ibrahim, Aisha; Bashir, Usman; Aliyu Abulfathi, Aisha; Sambo, Hassan (International Journal of Research in Medical Sciences, 2025)
Background: Childbirth poses significant risks, particularly in Nigeria where many births occur outside health facilities and without skilled attendants, skyrocketing maternal morbidity and mortality. This study assessed and compared place of delivery and its determinants among women in urban and rural Kano State. Methods: A cross-sectional study was conducted. A multistage sampling technique selected 292 urban and 300 rural women of reproductive age group. Quantitative data were analysed using SPSS 20. Results: Overall, 32.1% of women delivered in health facilities, while 67.9% delivered at home. Hospital deliveries were higher in urban (39.7%) than rural areas (24.7%). Safety, avoidance of problems, and trust in health workers facilitate hospital delivery. Conversely, customs, quick labour, and fear of hospital staff were major reasons for home delivery. Mother’s education (Urban: aOR; 3.023 (95% CI; 1.459-6.264), p=0.003), (Rural: aOR; 2.311 (95% CI; 1.106-4.829), p=0.026) and spousal education level (Urban: aOR; 2.925 (95% CI; 1.357-6.306), p=0.006), (Rural: aOR; 2.183 (95% CI; 1.241-3.840), p=0.007) remained predictors in both areas with secondary and above likely to deliver in hospital. While occupation was significant in the urban communities (aOR; 2.392 (95% CI; 1.137-5.031), p=0.022), antenatal care visits in the rural communities (aOR; 2.427 (95% CI; 1.408 - 4.367), p=0.001). Conclusions: The study found a high proportion of home deliveries with associated sociodemographic and socio-economic factors. Emphasis on hospital delivery and addressing sociodemographic and socioeconomic factors facilitating home deliveries is recommended.